FAKTOR PADA PERAWAT YANG BERHUBUNGAN DENGAN PERSEPSI MELAPORKAN KEJADIAN TIDAK DIHARAPKAN (KTD) DI RUMAH SAKIT PRIMA MEDIKA DENPASAR TAHUN 2020 - Wirama, I Putu; Wibowo, Adik (UI Scholars Hub, 2022)
Hospital is complex and full of risk medical facility. Adverse events reporting is one part of the patient safety system that has an important roles to improve the hospital’s quality. Nurses have the longest contact's time with patients so they become the most important component in reporting the Adverse Event Reporting. This study aims to determine the factors that affects perception in adverse event reporting at Prima Medika Hospital Denpasar 2020. Prima MedikaHospitalis a type C private hospital.This studies quantitative study using a cross- sectional design with 140 nurses as samples and conducted in June 2020. The nurses’s perception who never report adverses event is 63.6%, assuming they never found any adverse event or maybe have found it but not have no courage to report it. The variable that significantly associated with perceptions on adverse event reporting by nurse are attitude (p value=0.002), education(p value=0.046), and workload ( heavy workload with p value=0.003 and light workload with p value=0.026). The most affecting variable is the nurses attitude (OR 4.33). It is proposed for the hospital to build the nurses positive attitude to report adverse events one through giving appreciation to those who report the adverse event, hospital needs to give regular patient safety training to maintain the nurse knowledge, and to revisit the 12-hour nightshift which is regarded as unusual long hours.